Canva Learning Media to Improve Students’ Learning Achievement in the Merdeka Curriculum - Prihantini, Prihantini; Istianti, Tuti; Rukmini, Ai; Sutarto, Sutarto (International Journal of Membrane Science and Technology, 2023)
Changes and developments in technology have brought the world of education involved in the utilization of these technologies. In today’s digital era, it will never be separated from how efforts to improve the performance of the world of education by utilizing technology and applications. One of the most popular applications in the current disruption era that can be used to support educational operations is Canva. Canva is an online-based application that provides design templates and attractive features. The purpose of this study is to describe learning methods using Canva applications effectively enough to improve student learning achievement in the independent curriculum. This research uses quantitative methods, data obtained through distributing questionnaires. The questionnaire was distributed using the Google Form application. The results of this study explain that the use of Canva as a learning media can explore the creativity side of educators and improve student achievement in the teaching and learning process, create interesting learning materials so that they can arouse student interest in learning and lead to better learning outcomes. The conclusion of this study explains that Canva learning media greatly influences the process and learning outcomes of students in the independent curriculum. The limitations in this study are that researchers have difficulty in deepening the data, the time of data collection which takes a long time, and high subjectivity. This study also recommends that future researchers be able to conduct further and in-depth studies on the utilization of this canva learning media.